Morfometrik tubuh kambing Peranakan Ettawa pada berbagai paritas di balai Pembibitan dan Budidaya Ternak Terpadu Kabupaten Kendal - Dwi Purwanti; Enny T. Setiatin; Edy Kurnianto (Faculty of Animal Science, Universitas Brawijaya, 2019)
The objective of this study was to determine the relation between morphometric of different parity and litter size in Ettawa Grade goat. The material of this study was 47 heads of Ettawa Grade goat. Purposive sampling was applied to determine sample based on population and breeding policy. The Ettawa Grade used were does from1-4 parities and having litter size records from first kidding. Morphometric characteristics measured were chest depth, chest width, hip width, hip height, heart girth, body length, and withers height. The data obtained were analyzed using General Linear Model (GLM) and Principal Component Analysis (PCA) of Statistycal Analysis System (SAS) Ver 6.12. The results showed that morphometric of Ettawa Grade goat was vary and different in various parity. The PC1 of body length and heart girth were 0.685 and 0.530 respectively, indicating the most discriminant variabel to determine the differences among parity. Body index of Ettawa Grade goat does did not affect the litter size. In conclusion, body length and heart girth can be used as the differentiation parameter among parity. Litter size will increase with increasing parity.